Nursing Process in Central Java Correctional Institutions: Qualitative Descriptive Study - Abdullah Azam Mustajab; Megah Andriany; Elis Hartati (Poltekkes Kemenkes Surakarta, 2026)
Background: Correctional institution nurses in carrying out the nursing process differ from other specialist nurses who work outside the correctional institution facility. A lot of research on the nursing process has been carried out in hospital and puskesmas settings. However, few research is found in the correctional institution setting. The purpose of the study was to describe the implementation of the nursing process in the Central Java Correctional Institution. Methods: The researcher used a qualitative study with a qualitative descriptive approach. Data collection was done online using semi-structured interview guidelines about the nursing process in correctional institutions with a duration of 30 minutes. Study participants were saturated with nine participants of nurses. Data trustworthiness using Guba's idea technique and data analysis in this study used the analytical procedures of Zhang and Wildemuth. Results: In this study, the researchers described several themes based on the research objectives. The five objective themes are conducting record of health checks for new inmates, no standardization of nursing care, regulations in providing services to inmates, the implementation of individual and group nursing care, and collaboration with agencies outside prisons and detention centers. Conclusion: The findings of this study need to get attention from all parties such as the Ministry of Law and Human Rights and Indonesian National Nurses Association (INNA) to maintain the quality-of-care services for inmates. Furthermore, the quality of prison nurses in carrying out nursing practices also should be confirmed in line with nursing professional standards.